Incidence and risk factors associated with ectopic pregnancy: a prospective study - K. M., Harish; N., Shwetha; N., Nalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Increased incidence of ectopic pregnancy and its impact on women’s fertility in recent years need significant attention. Methods: A two years prospective study from January 2018 to December 2019 conducted to determine incidence, association of risk factors with ectopic pregnancy and find the most common risk factor of ectopic pregnancy in department of obstetrics and Gynaecology, a tertiary care Hospital in Pune. Results: During the study period 100 patients were diagnosed to have ectopic pregnancy. Incidence was 5.29 per 1000 births. Majority were in the age group of 20-24 years (42%), multiparous (59%) and belong to low socioeconomic state (62%). In majority of the patients (22%) no risk factors was found. Among the patients who had risk factors, the main risk factors for ectopic pregnancy were history of history of pelvic inflammatory disease (20%), previous tubal/abdominal surgery (12%), history of Infertility (10%), previous termination of pregnancy (10%), contraception with mirena IUS or IUCD in situ (8%) and a history of prior ectopic pregnancy (4%). Conclusions: In majority (78%) of patients risk factors for ectopic pregnancy was present and pelvic inflammatory disease was found to be a major risk factor for ectopic pregnancy.